Proceedings - The Tenth International Symposium GRID 2020 2020
DOI: 10.24867/grid-2020-p37
|View full text |Cite
|
Sign up to set email alerts
|

Research methodologies for assessing the ergonomics of packaging products - A review

Abstract: In today’s increasingly competitive market environment, new packaging must meet more requirements than before to meet customer expectations. The packaging must meet not only functional and aesthetic requirements but also ergonomic requirements to ensure satisfying user experience. An important issue in ergonomic design is the identification of factors that lead to user comfort and discomfort. The packaging is a product that undergoes manual manipulation and given the various forms of packaging and it's opening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Whilst CRCs safeguard children against drug intoxication, reported feedback indicates that consumers find difficulty using them. 4,5 Further studies have revealed CRCs openability challenges as a major problem faced by consumers especially the older generation, rheumatoid and osteoarthritis patients and even the general population in different regions around the globe. [4][5][6][7][8][9][10][11] The inability of some patients to open CRC packages in a controlled or safe manner has been attributed to inadequate, incomprehensible or misleading opening instructions.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Whilst CRCs safeguard children against drug intoxication, reported feedback indicates that consumers find difficulty using them. 4,5 Further studies have revealed CRCs openability challenges as a major problem faced by consumers especially the older generation, rheumatoid and osteoarthritis patients and even the general population in different regions around the globe. [4][5][6][7][8][9][10][11] The inability of some patients to open CRC packages in a controlled or safe manner has been attributed to inadequate, incomprehensible or misleading opening instructions.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Further studies have revealed CRCs openability challenges as a major problem faced by consumers especially the older generation, rheumatoid and osteoarthritis patients and even the general population in different regions around the globe. [4][5][6][7][8][9][10][11] The inability of some patients to open CRC packages in a controlled or safe manner has been attributed to inadequate, incomprehensible or misleading opening instructions. 7,12 Opening limitations have been indicated to prevent patients from accessing medications and result in their noncompliance, prohibiting the prescribed regimen from achieving maximal therapeutic benefit.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations